'It's just a very personal thing': contraceptive influences and decision making among women living in Italy. (4th May 2019) - DeMaria, Andrea L.; Rivera, Sydney; Ramos-Ortiz, Jaziel; Meier, Stephanie; Wakefield, Audrey L.; Basile, Kelsie; Evans, Jalynn M.; Zaininger, Hannah Marie; Clayton, Anyia
Abstract: Objective: The purpose of the study was to assess contraceptive knowledge, perceptions and experiences among reproductive-aged women in Italy. Methods: As part of a larger mixed-methods study, researchers conducted 46 interviews (June–July 2017) with English-speaking women aged 18–45 living in or near Florence, Italy, who were using the Italian health care system. Researchers used grounded theory to explore women's contraceptive decision making and use. HyperRESEARCH software was used to aid data organisation and analysis. Researchers used a comparative method to contextualise data and identify emergent themes. Results: Participants illuminated knowledge gaps and misinformation about the efficacy and long-term health effects of hormonal contraceptive methods. Family, friends and health care providers influenced their contraceptive choices. Local family planning clinics ( consultori ) were cited as primary sources of contraceptive information, resources and access. Conclusion: Misinformation may contribute to the underuse of effective hormonal contraception in Italy. The study findings can inform practical recommendations to improve the dissemination of contraceptive information. Improved messaging strategies could address contraceptive concerns (e.g., hormonal effects) and knowledge gaps, which may improve hormonal contraceptive uptake.